2016
DOI: 10.1111/1750-3841.13235
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Bioaccessibility of Curcuminoids in Buttermilk Yogurt in Comparison to Curcuminoids in Aqueous Dispersions

Abstract: Curcuminoids have low bioavailability due to low aqueous solubility. We compared the bioaccessibility of curcuminoids delivered in buttermilk yogurt to that of curcuminoid powder in an aqueous dispersion. Buttermilk containing added curcuminoids (300 mg/100 g, 0.3% w/w) was used for yogurt manufacture. We measured percentage of curcuminoids remaining in yogurts after manufacture and after exposure to simulated gastrointestinal fluids, and the in vitro bioaccessibility of the curcuminoids. Curcuminoids were sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…The initial pH of faecal slurry was at pH 6.9, but after 24 h of fermentation, the pH was decreased in all samples. As expected, the decrease in pH was more pronounced for DSP yoghurt, due to continuing activity of lactic acid bacteria from the yoghurt on the yoghurt contents (Fu et al ., ). Aerobic and anaerobic bacterial counts in the original faecal slurry were 4.92 ± 0.05 and 8.61 ± 0.10 log 10 CFU mL −1 , respectively.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…The initial pH of faecal slurry was at pH 6.9, but after 24 h of fermentation, the pH was decreased in all samples. As expected, the decrease in pH was more pronounced for DSP yoghurt, due to continuing activity of lactic acid bacteria from the yoghurt on the yoghurt contents (Fu et al ., ). Aerobic and anaerobic bacterial counts in the original faecal slurry were 4.92 ± 0.05 and 8.61 ± 0.10 log 10 CFU mL −1 , respectively.…”
Section: Resultsmentioning
confidence: 97%
“…Nonetheless, bioaccessibility of polyphenols from food matrixes and their bioavailability, which is affected by chemical stability and absorption kinetics in the gastrointestinal tract, metabolic modification in the liver and pharmacokinetics of plasma clearance, are the major determinants of the health efficacy of polyphenols from foods or as supplements. For example, the interactions of polyphenols with food matrix components such as proteins, lipids and dietary fibre that influenced their accessibility and chemical stability for intestinal absorption and colonic fermentation have been widely documented (Oliveira & Pintado, 2015;Fu et al, 2016;Mandalari et al, 2016) and that polyphenol glycosylation and esterification also impact on their bioavailability (Scalbert et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…In any case, the clearest effect of lipid matrices can be expected on lipophilic compounds, such as curcuminoids. Fu et al (2016) found enhanced curcuminoid bioaccessibility in buttermilk yogurt in comparison to aqueous dispersions, due to better micellarization during digestion.…”
Section: Lipid Interactionsmentioning
confidence: 88%
“…The in vitro colonic fermentation procedure was carried out according to the protocol of Fu, et al [14] with modifications. Pig faeces were used as sources of gut microbiome as a substitute of human faeces, as pigs and humans are primarily colonic fermenters sharing a comparable gut microbiome [15].…”
Section: In Vitro Colonic Fermentationmentioning
confidence: 99%